Influence of Organic Solvent on the Physicochemical Characteristics of Calcium Citrate Prepared from Mussel Shell Waste - Sirichet Punthipayanon; Pantita Chanwetprasat; Somkiat Seesanong; Banjong Boonchom; Pesak Rungrojchaipon; Nongnuch Laohavisuti; Wimonmat Boonmee (Processes, 2025)
A green and mild chemical reaction of calcium citrate (CC) was successfully prepared from reactions between mussel shell waste and citric acid in the presence of acetone (AC), ethanol (Et), and isopropyl alcohol (IPA). All the synthesized CCs contained the same functional groups such as citrate (C6H5O73−), water (H2O), and calcium–oxygen (Ca–O). However, the differences in the spectra pointed out the differences in the crystal environment and structure of CCs. CC-AC and CC-IPA mainly crystallized in the monoclinic [Ca3(C6H5O7)2(H2O)2]·2H2O crystal system, whereas CC-Et mainly crystallized in the triclinic Ca3(C6H5O7)2∙(H2O)4 structure. The molecular alignments of triclinic CC-Et were different from monoclinic CC-AC and CC-IPA, resulting in differences in thermal behaviors. Two dehydration steps were observed for the monoclinic CC-AC and CC-IPA, whereas the triclinic CC-Et showed a single dehydration process. The TG mass losses further demonstrated that anhydrous Ca3(C6H5O7)2 phase, in addition to the Ca3(C6H5O7)2∙4H2O, was also observed for CC-AC and CC-IPA, whereas CC-Et contained a single Ca3(C6H5O7)2∙(H2O)4 phase. The morphologies of CC-AC and CC-IPA also differed from that of CC-Et. The differences in some properties of the synthesized CCs could be attributed to the change in the supersaturation state of the reaction solution. Due to the superior polarity, ethanol is more compatible with citric acid. The presence of ethanol could suppress the supersaturation rate of the reaction solution, causing the modulation of the precipitation mechanisms and reducing the particle growth rate of CC-Et, thereby explaining the difference in vibrational, structural, thermal, and morphological characteristics of CC-Et, compared to CC-AC and CC-IPA.
Keywords: Materials Engineering and Processing; Bone Tissue Engineering Materials; Adsorption and biosorption for pollutant removal